2012
DOI: 10.1001/archinternmed.2012.3004
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry-Containing Products for Prevention of Urinary Tract Infections in Susceptible Populations

Abstract: Our findings indicate that cranberry-containing products are associated with protective effect against UTIs. However, this result should be interpreted in the context of substantial heterogeneity across trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
152
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(158 citation statements)
references
References 24 publications
0
152
0
6
Order By: Relevance
“…19 A Cochrane review reported a UTI reduction of 35% (95% CI = 10-54%). 17 In the recent update of this Cochrane review in 2012, the authors performed a meta-analysis based on two studies evaluating cranberry in elderly adults (N = 413).…”
Section: Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A Cochrane review reported a UTI reduction of 35% (95% CI = 10-54%). 17 In the recent update of this Cochrane review in 2012, the authors performed a meta-analysis based on two studies evaluating cranberry in elderly adults (N = 413).…”
Section: Effectivenessmentioning
confidence: 99%
“…17,18 Another recent systematic review indicates that cranberry-containing products are associated with a protective effect against UTI in different subgroups, albeit with heterogeneity across the included trials. 19 A recent study in children without urological abnormalities showed a 65% reduction of UTI with the use of cranberry.…”
mentioning
confidence: 98%
“…The most recent two meta-analyses have come to different conclusions. While Jepson et al 47 in their Cochrane Review concluded that there was no evidence for cranberries to prevent UTI, Wang et al 48 found a weak evidence after having excluded one trial as a negative outlier. 49 However, critics rightly argued that this maneuver had caused a bias, as data from a positive outlier study had still been analyzed.…”
Section: The Mixed Evidence From Clinical Trialsmentioning
confidence: 99%
“…Cranberry products (juice, tablets, capsules) have been used widely for the prevention and treatment of UTIs. 24,25 However, current evidence does not support their use and they are no longer recommended for the prevention of recurrent UTIs. 26 Oestrogen products (for postmenopausal women) and methenamine hippurate are also not recommended as there is no good evidence to support their use for preventing recurrent UTIs.…”
Section: Recurrent Bacterial Uti In Womenmentioning
confidence: 99%